Plasmodium malariae Infection Associated with a High Burden of Anemia: A Hospital-Based Surveillance Study. - Siobhan Langford; Nicholas M Douglas; Daniel A Lampah; Julie A Simpson; Enny Kenangalem; Paulus Sugiarto; Nicholas M Anstey; Jeanne Rini Poespoprodjo; Ric N Price (Public Library of Science (PLoS), 2015)
BACKGROUND:Plasmodium malariae is a slow-growing parasite with a wide geographic distribution. Although generally regarded as a benign cause of malaria, it has been associated with nephrotic syndrome, particularly in young children, and can persist in the host for years. Morbidity associated with P. malariae infection has received relatively little attention, and the risk of P. malariae-associated nephrotic syndrome is unknown. METHODOLOGY/PRINCIPAL FINDINGS:We used data from a very large hospital-based surveillance system incorporating information on clinical diagnoses, blood cell parameters and treatment to describe the demographic distribution, morbidity and mortality associated with P. malariae infection in southern Papua, Indonesia. Between April 2004 and December 2013 there were 1,054,674 patient presentations to Mitra Masyarakat Hospital of which 196,380 (18.6%) were associated with malaria and 5,097 were with P. malariae infection (constituting 2.6% of all malaria cases). The proportion of malaria cases attributable to P. malariae increased with age from 0.9% for patients under one year old to 3.1% for patients older than 15 years. Overall, 8.5% of patients with P. malariae infection required admission to hospital and the median length of stay for these patients was 2.5 days (Interquartile Range: 2.0-4.0 days). Patients with P. malariae infection had a lower mean hemoglobin concentration (9.0 g/dL) than patients with P. falciparum (9.5 g/dL), P. vivax (9.6g/dL) and mixed species infections (9.3g/dL). There were four cases of nephrotic syndrome recorded in patients with P. malariae infection, three of which were in children younger than 5 years old, giving a risk in this age group of 0.47% (95% Confidence Interval; 0.10% to 1.4%). Overall, 2.4% (n = 16) of patients hospitalized with P. malariae infection subsequently died in hospital, similar to the proportions for the other endemic Plasmodium species (range: 0% for P. ovale to 1.6% for P. falciparum). CONCLUSIONS/SIGNIFICANCE:Plasmodium malariae infection is relatively uncommon in Papua, Indonesia but is associated with significant morbidity from anemia and a similar risk of mortality to patients hospitalized with P. falciparum and P. vivax infection. In our large hospital database, one in 200 children under the age of 5 years with P. malariae infection were recorded as having nephrotic syndrome.